The Income Distribution as a Pure Public Good - Thurow, Lester C. (Quarterly Journal of Economics, 1971)
I. The optimum income distribution from a voluntary theory of exchange, 329. — II. A complication, 333. — III. The mathematics, 333. — IV. Conclusions, 335.